Differences in aluminum tolerance of populus genotypes : development of methodology for identification of poplar genotypes suitable for acidic forest land - Arlauskas, Mikas (SLU/Southern Swedish Forest Research Centre, 2020)
Forest lands hold great potential for Populus plantations for bionenergy purposes. However in native boreal forests where land for establishing these plantations is abundant poplars encounter challenges in establishment. One of these challenges is aluminum (Al) - one of the major factors hindering plant growth by inhibiting root growth, thus reducing water and nutrient uptake and slowing growth. Forest soils normally have low pH and thus higher levels of aluminum ions (Al3+ and hydroxides). However there is evidence of Al tolerance among Populus species thus if succsessfully identified, could be able to grow on forest sites. The aim of the study is to evaluate growth response of Populus hybrids to different of aluminum concentrations and identify the type of data should be collected if the clones with differences in Al should be identified. In this study, growth responses of greenhouse-grown poplar (P. trichocarpa hybrids) were monitored in relation to changes in Al concentrations in quartz sand. The results identified several poplar clones which were more tolerant and most susceptible to Al. The differences in Al sensitivity were identified by measurements of relative stem growth, root biomass and supported by staining with hematoxylin for root damages. The findings suggest that identification of Al tolerant Populus clones requires several steps of data collection. What is more, further experimentation is required to fully confirm that the selected clones are truly capable of establishment on forest sites with investigation of those sites soil properties.